HAZARD RISK MANAGEMENT, BUILDING TREE - Donchenko, Dmytro; Stefanovych, Ivan; Stefanovych, Pavlo (SWorld-Ger Conference proceedings, 2023)
The main aspects of risk management are provided in detail, as well as the method of constructing a failure tree as an effective tool for analysis and modeling